Política de indexação em repositórios institucionais de instituições federais da região sudeste do Brasil: estudo analítico - Andrade, Guilherme Francisco Sposito de (Universidade Federal de São Carlos, 2021)
Indexing was one of the areas of Library Science and Information Science that has evolved the most over the years, due to technological advances and adaptation to the behavior of users. Currently, with the use of Institutional Repositories, in accordance with Open Science guidelines, users have become authors and indexers of their works simultaneously. Thus, it is necessary to standardize the indexing to guarantee access and use of information. In this sense, this research questions what are the guidelines for the representation of content in institutional repositories that adopt self-archiving. The objective, therefore, is to investigate the existence of indexing policies in institutional repositories, in order to contribute to the representation of contents in hybrid systems that adopt the practice of self-archiving. This is an exploratory and descriptive work, conducted through bibliographical research and survey. It appears that only one institution has an indexing policy, dating from 2021. Another five institutions do not have an indexing policy, but allude to them in their self-archiving materials. It is concluded that the field of study is very recent and has been gaining space in scientific and technical discussions, making public the importance of elaborating an indexing policy that meets the requirements of the self-archiving process and the precepts of Open Science.
Indexing policy in institutional repositories of federal institutions in the southeast region of Brazil: analytical study
Keywords: Política de indexação; Repositório Institucional; Instituições federais; Ciência aberta; Região Sudeste – Brasil; Indexing policy; Institutional repositories; Federal universities; Open science; Southeast Region – Brazil; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA